Media Sosial Anggota DPRD DKI Jakarta untuk Membangun Citra dan Transparansi Kinerja Lembaga - Daffa Dhiyaul Haq Machmudi; Nurdin Sibaweh (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the role of social media used by members of the Jakarta Regional House of Representatives (DPRD DKI Jakarta) in building institutional image and enhancing transparency of public performance. The study is motivated by the rapid growth of social media as a public communication platform that requires government institutions to be more open, accountable, and responsive to public demands. This research employs a qualitative descriptive approach based on an internship (Praktik Kerja Lapangan) program conducted at the Jakarta DPRD. Data were collected through observation, interviews, direct participation, and documentation during the internship period. The findings indicate that social media platforms, particularly Instagram and TikTok, function as strategic communication channels for disseminating information related to legislative activities, including plenary meetings, recess activities, working visits, and social programs. Well-managed content that is consistent, informative, and visually structured contributes to increased public engagement and supports the formation of a professional and transparent institutional image. The application of Information Integration Theory and the Social Media Engagement Behavior model demonstrates that audiences integrate various pieces of information received through social media to construct perceptions of institutional performance.The originality of this study lies in the integration of practical internship experience with communication theory analysis within the context of digital media management in a regional legislative institution. The results are expected to provide insights for public institutions in developing effective digital communication strategies to strengthen public trust and participation